2023
DOI: 10.3390/d15050633
|View full text |Cite
|
Sign up to set email alerts
|

Fern Cave: A Hotspot of Subterranean Biodiversity in the Interior Low Plateau Karst Region of Alabama in the Southeastern United States

Matthew L. Niemiller,
Michael E. Slay,
Thomas Inebnit
et al.

Abstract: The Fern Cave System, developed in the western escarpment of the Southern Cumberland Plateau of the Interior Low Plateau karst region in Northeastern Alabama, USA, is a global hotspot of cave-limited biodiversity as well as home to the largest winter hibernaculum for the federally endangered Gray Bat (Myotis grisescens). We combined the existing literature, museum accessions, and database occurrences with new observations from bioinventory efforts conducted in 2018–2022 to generate an updated list of troglobio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%
See 2 more Smart Citations
“…Lukić et al [36] reported that almost all information for the fauna of the Lukina Jama-Trojama Cave System in Croatia dates from the 1990s or later. The same is true for Fern Cave in Alabama [44], Hon Chong in Vietnam [46], and the Água Clara Cave System in Brazil [27,28]. Sampling effort is therefore a major determinant of the richness of species in these caves.…”
Section: Taxonomic Completenessmentioning
confidence: 88%
“…They point out that the ridge is the area of highest secondary productivity in Europe. Such a ridge of high biodiversity does not occur in North America, but there is a small area near the combined border of Tennessee, Alabama, and Georgia of similarly high biodiversity and presumed high secondary productivity [15,43,44]. More generally, a difference between Europe and North America is that European mountain ranges are often oriented east-west while North American mountains are north-south in orientation.…”
Section: The Emerging Global Pattern and Its Causesmentioning
confidence: 99%
See 1 more Smart Citation
“…The cave-limited fauna of the Crystal-Wonder Cave System is remarkably diverse with 31 troglobionts and stygobionts, making it the most diverse cave system in the southern Cumberland Plateau region, and one of the most diverse cave systems in all of North America. With 31 cave-limited species, the Crystal-Wonder Cave System trails only the San Marcos artesian Well in central Texas (55 species; [85]) and the Mammoth Cave System in central Kentucky (49 species; [86]) and ranks ahead of the Fern Cave System in Alabama (27 species; [10]) and Sistema Huautla in Oaxaca, Mexico (27 species; [87]). In particular, the terrestrial fauna is exceptionally rich with 23 species, trailing only the Mammoth Cave System (32 troglobionts; [86]) and Sistema Huautla (27 species; [87]) in North America.…”
Section: Discussionmentioning
confidence: 99%
“…Several cave systems support a significant biodiversity at the local scale, including 19 caves with >12 cave-limited (i.e., permanent inhabitants of subterranean habitats) species documented [2,8], Niemiller and Zigler, unpublished data]. In particular, two cave systems in the southern Cumberland Plateau region have been recognized as hotspots for cave-limited biodiversity [sensu 9]: Shelta Cave in Madison County, Alabama with 24 species [9], and Fern Cave in Jackson County, Alabama with 27 species, respectively [10]. Here, we add a third cave system-the Crystal-Wonder Cave System in Grundy County, Tennessee-that is the most speciose cave system with respect to the cave-limited fauna in the southern Cumberland Plateau.…”
Section: Introductionmentioning
confidence: 99%